Desenvolvimento de simuladores de mama para controle de qualidade e treinamento - Alves, Anderson Vinicius Silva (2015)
Breast cancer is the type of cancer that affects more women worldwide. Its early detection is key to achieve its treatment and, consequently, reduce its mortality rate. Mammography is considered the most suitable technique for this detection, which is based on the visualization of small structures and patterns that may represent cancerous lesions. But for visualization of these structures, the quality control of mammographic images and the training of residents and radiologists is required. With this in mind, this study aimed the development and confection of three breast simulators (phantoms) that serve these purposes. The materials used in this construction were analyzed and their attenuation coefficients were compared to simulated breast tissues. The phantoms were prepared in polymethylmethacrylate molds and plates, known as acrylic, and the test structures used were microcalcifications, simulated by limestone, and fibers, simulated by nylon. The phantoms I-a and I-b are intended to perform quality control and has its test structures placed in a mixture of paraffin gel and acrylic powder and dental wax, respectively. The phantom II is intended to conduct the training of residents and radiologists and has its test structures placed in dental wax. The detectability of the test structures was variable with the thickness of phantoms. After analysis and comparison of results between the phantoms made and the marketable phantom recommended by the national standard, made phantoms were validated.